If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 10y = 50 Solving 6x + 10y = 50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10y' to each side of the equation. 6x + 10y + -10y = 50 + -10y Combine like terms: 10y + -10y = 0 6x + 0 = 50 + -10y 6x = 50 + -10y Divide each side by '6'. x = 8.333333333 + -1.666666667y Simplifying x = 8.333333333 + -1.666666667y
| x^3-9x^2+22x-15=0 | | 3n^2-5=0 | | 34-3w=25 | | 8x(8x-7)+-8x(9x-8)= | | 4-1/2 | | -50+87x=-75x^2-8x | | 8m^2+5m+4=7+3m | | 1/2*1/4 | | u+12u+17=0 | | x*x^3*x^3= | | (b^2+3b-9)/(b+5) | | 8/c+2-6=4/c+2 | | C(c+2)=12 | | W(w-5)=14 | | 6z-15=3z+12 | | t^2/2+2t=-1/4 | | 1/4(8-8x)=1/2(4x+2) | | 7+4(z-8)=3-3z | | 3x-6=2x+15 | | x-10x+25=0 | | (4v-6)(1+v)=0 | | 99.08/100*40.65=x | | 8n=6-14 | | 5x-2-7x=4+x-1 | | -2x-1/16=-6x^2 | | 56=4h/7 | | X^4-12x^4+48x^2-64=0 | | -7w=-91 | | -22=-p | | 8t-20=6t+10 | | 15n^2+19n+6=10+2n | | 3x^2+10x+15=-4X |